STRUCTURAL AND ELECTROCHEMICAL PROPERTIES OF SYNTHESIZED NANOSTRUCTURED Ca0.9Er0.1MnO3 BY HYDRAZINE NITRITE PROCEDURE - Vlašković, Tijana B.; Rosić, Milena; Petković, Branka B.; Laban, Bojana B. (Bulletin of Natural Sciences Research, 2025)
Synthesis, structural, and electrochemical properties of nanostructured powders Ca0.9Er0.1MnO3 with perovskite-type crystal were studied. Nanopowders were prepared by the combustion method using the hydrazine nitrite procedure (HNP), which involves mixing metal nitrate salts (Ca, Mn, Er) in a stoichiometric ratio and varying the quantity of added hydrazine. In this synthetic procedure, the aim is to adjust the amount of hydrazine in order to control the combustion of the reactions, obtain the required amount of fuel energy, but also the amount that will complex the reactants in the mixture. The powders obtained by hydrazine nitrate synthesis were then calcined for 15 minutes at temperatures of 800, 900, and 1000 °C. Characterization of the synthesized and calcined samples was performed using advanced techniques such as X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and electrochemical measurements. The results clearly indicate that the amount of hydrazine added is crucial in preparing the Ca0.9Er0.1MnO3 sample. This highlights the importance of precise hydrazine dosage in optimizing the synthesis process to enhance the material’s properties. Further, the electrochemical properties of the obtained perovskite nanopowders were investigated by cyclic voltammetry (CV) and electrochemical spectroscopic impedance (EIS) on perovskite-modified carbon paste electrodes. Electrochemical measurements showed improved electrochemical properties of perovskite-modified carbon paste electrodes compared to bare carbon paste electrode (CPE). The electrode modified with the material synthesized with the smallest amount of hydrazine presented the best results.